Involving children in disaster risk reduction: the importance of participation. (3rd December 2018) - Pfefferbaum, Betty; Pfefferbaum, Rose L.; Van Horn, Richard L.
ABSTRACT: Background : Millions of children are affected by disasters every year. Children need not be passive victims, however, but instead may contribute to disaster risk reduction activities. Objective : This paper provides a theoretical foundation for children's involvement in disaster risk reduction activities. Method : The paper reviews and analyses the literature on children's participation, on their developmental capacity to participate, and on disaster risk reduction activities involving children. Results : Participation yields numerous potential benefits for children, including enhanced personal development and skills, self-efficacy, and interpersonal relationships, and for communities through improved social connections and networks and disaster preparedness. Conclusions : Children are resources to be cultivated and mobilized for disaster preparedness, response, recovery, and resilience. Attention is needed to identify approaches to appropriately enlist, engage, and involve children in disaster risk reduction activities; to promote these efforts; and to evaluate these approaches.